Pertumbuhan Tongkol Jagung Baby Corn (Zea Mays L.) Varietas Pioneer-11 Setelah Pemberian Kascing - Nurchayati, Yulita; Yuliana, Titis (JURNAL SAINS DAN MATEMATIKA, 2006)
ABSTRACT—An experiment to obtain high productivity of baby cornâ€™s cob by casting treatment has been conducted. The aims of this experiment were to study the casting effect for baby corn productivity and to obtain the efficient dose of casting to increase baby corn productivity. This experiment was done by a Randomized Complete Design with four treatment and seven replication. The treatments were four kinds of casting dose, i.e 0g/plant, 200g/plant, 400g/plant and 600g/plant in their growth media. The measurable parameter were fresh weights, dry weights and cob quantity of baby corn. The casting was analyzed qualitatively including C/N ratio and organic material of casting. The result showed that the casting can increase the cob of baby corn productivity eventhough the efficient doses of casting to increase the baby corn productivity were not obtained. Â Keywords: baby corn, casting, cob